Reformulasi Prosedur Perlindungan Dalam Undang-Undang Penghapusan Kekerasan Dalam Rumah Tangga Yang Tidak Efektif - Aroma Elmina Martha; Endah Rizki Ekwanto (Lex Renaissance, 2019)
Law No. 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT) explains that domestic violence (KDRT) is an act against a person - especially a woman - which results in physical, sexual, psychological, and/or neglect of the household including threats to commit acts, coercion or deprivation of liberty unlawfully and within the scope of the household. Thus UU PKDRT is a guarantee offered by the state to prevent, protect, and follow up on perpetrators of domestic violence, but it is not effective. This research aims to examine the ineffectiveness and seek the appropriate reformulation of the articles. This is a juridical-sociological research using the analysis approach on UUKDRT. The results of this study indicate that there are inefficiencies in the articles contained in the UUPKDRT, especially in terms of protection caused by several factors both from the community itself and from law enforcement officials.